2016
DOI: 10.4103/2249-4863.192356
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care; role of family physicians

Abstract: Palliative care is the holistic approach to provide relief to patients suffering from life threatening diseases and their families throughout the disease. This is mainly through the prevention and relief of suffering by means of early identification, comprehensive assessment and management of physical, psychosocial and spiritual problems. With the rise of elderly population in the world patients needing palliative care will also increase. Family physicians who are closest to the community and easily accessible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 2 publications
0
77
0
6
Order By: Relevance
“…1,2 Caring for people nearing the end of their lives is considered a part of the core business of general practice. 3,4 Palliative care can improve the quality of life of patients facing problems associated with life-limiting conditions through the prevention and relief of suffering. It can also reduce the use of futile treatment and caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Caring for people nearing the end of their lives is considered a part of the core business of general practice. 3,4 Palliative care can improve the quality of life of patients facing problems associated with life-limiting conditions through the prevention and relief of suffering. It can also reduce the use of futile treatment and caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in US family doctors are significantly more likely to provide non-clinic-based palliative care services [3]. Their role is to communicate and coordinate with other health care resources to address complex issues faced by patients [16]. Moreover, researchers have found that family doctors' tasks and roles are to ensure the integration of palliative care and collaboration [17].…”
Section: Resultsmentioning
confidence: 99%
“…Results also show that the communication and exchange of information between those specialists and information provided to patients and their family members are crucial to ensure the patient needs and to improve the palliative care. Indeed, as stated by Ramanayake, developing palliative care models should include opportunities for family doctors to learn sound palliative care principles in order to meet the challenges of the future [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it indicates the specificity of palliative patient and the involvement of family members in decision making for such patients. On the other hand, the cumulative analysis of hospital admissions shows an inadequate cooperation, discoordination between various levels of health care and, principally, the organizational imperfection of primary medical care that should determine the patient's route and act as a coordinator for providing medical and nonmedical needs to both incurably ill patients and their families [14,15].…”
Section: Resultsmentioning
confidence: 99%